2012
DOI: 10.1143/apex.5.055504
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Freestanding AlN Substrate from a Thick AlN Layer Grown by Hydride Vapor Phase Epitaxy on a Bulk AlN Substrate Prepared by Physical Vapor Transport

Abstract: The structural and optical quality of a freestanding AlN substrate prepared from a thick AlN layer grown by hydride vapor phase epitaxy (HVPE) on a bulk (0001)AlN substrate prepared by physical vapor transport (PVT) were investigated. The prepared HVPE-AlN substrate was crack- and stress-free. High-resolution X-ray diffraction ω-rocking curves of symmetric (0002) and skew-symmetric (1011) reflections had small full widths at half maximum (FWHMs) of 31 and 32 arcsec, respectively. Deep-ultraviolet optical trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
101
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 13 publications
7
101
0
3
Order By: Relevance
“…It was also found that the Si and C impurity concentrations in the overgrown AlN layer reduced to half of those in the PVT-AlN substrates. In another study, [54] FWHM values as small as 31 and 32 arcsec have been reported for the (0002) and (101 1) reflections of ω-rocking curves, respectively, for 114 μm-thick HVPE-AlN, grown on a bulk PVT-AlN substrate. The HVPE-AlN has larger external optical transmittance in the DUV range compared to the PVT-AlN substrate, with a steep optical transmission cutoff at 206.5 nm (Figure 3), which was attributed to lower concentrations of carbon, and oxygen impurities, and VAl in the HVPE-AlN substrate.…”
Section: Growth and Optical Properties Of Bulk Aln For Duv Ledsmentioning
confidence: 93%
“…It was also found that the Si and C impurity concentrations in the overgrown AlN layer reduced to half of those in the PVT-AlN substrates. In another study, [54] FWHM values as small as 31 and 32 arcsec have been reported for the (0002) and (101 1) reflections of ω-rocking curves, respectively, for 114 μm-thick HVPE-AlN, grown on a bulk PVT-AlN substrate. The HVPE-AlN has larger external optical transmittance in the DUV range compared to the PVT-AlN substrate, with a steep optical transmission cutoff at 206.5 nm (Figure 3), which was attributed to lower concentrations of carbon, and oxygen impurities, and VAl in the HVPE-AlN substrate.…”
Section: Growth and Optical Properties Of Bulk Aln For Duv Ledsmentioning
confidence: 93%
“…Different methods have been used to grow AlN with a low dislocation density such as physical vapor transport (PVT) [8], solution growth [9], thermal nitridation [10], metalorganic chemical vapor deposition (MOCVD) [11] and hydride (or halogen) vapor phase epitaxy (HVPE) [12,13]. The most successful methods to provide substrates of high structural quality are the PVT method [8] or a combination of PVT and HVPE methods [14,15]. They provide AlN substrates with low dislocation densities (<10 4 cm −2 ) able to be used for AlGaN-based deep UV light-emitting devices.…”
Section: Introductionmentioning
confidence: 99%
“…All the experiments described in Table 1 led to epitaxial growth on (0001) sapphire. No disorientation is observed and AlN presents its classical orientation AlN (0001)//sapphire (0001) and AlN //sapphire [11][12][13][14][15][16][17][18][19][20]. Cracks could be observed on the surface of some samples (see Table 2 for details).…”
mentioning
confidence: 95%
“…A number of groups fabricate bulk AlN single crystal using a sublimation method [1][2][3] and an alumina reduction method [4][5][6] . Recently, Kumagai et al 7) and Kangawa et al 8) grew AlN single crystal by the hydride vapor phase epitaxy method and Li 3 N solution growth method, respectively, using bulk AlN as a seed crystal fabricated by the sublimation method. Bockowski et al fabricated AlN crystals from Al melt at high temperature up to 2000 K and high N 2 pressure of order of 1 GPa without seed crystal 9) .…”
Section: Introductionmentioning
confidence: 99%